Intelligence and human rights in the era of global terrorism - Tsang, Steve Yui-Sang 1959- (Stanford Security Studies, an imprint of Stanford University Press, 2008)
Facing threats posed by dedicated suicide bombers who have access to modern technology for mass destruction and who intend to cause maximum human suffering and casualty, democratic governments have hard choices to make. This book addresses the question of how intelligence organizations can improve their efficacy in pre-empting terrorist outrages.